Stringent limits on 28SiO maser emission from the recurrent nova T Coronae Borealis. Issue 4 (11th June 2022) - Evans, A; Pimpanuwat, B; Richards, A M S; Banerjee, D P K; Munari, U; Gray, M D; Hutawarakorn Kramer, B; Kraus, A
ABSTRACT: There are indications that the third-known eruption of the recurrent nova T CrB is imminent, and multiwavelength observations prior to the eruption are important to characterize the system before it erupts. T CrB is known to display the SiO fundamental vibrational feature at 8 μ m. When the anticipated eruption occurs, it is possible that the shock produced when the ejected material runs into the wind of the red giant in the system may be traced using SiO maser emission. We have used the 100 m Effelsberg Radio Telescope to search for 28 SiO emission in the υ = 1, υ = 2, J = 1 → 0 transitions, at 43.122 GHz and 42.820 GHz, respectively, while the system is in quiescence. We find no evidence for such emission. We set stringent 3σ upper limits of 1.66 mJy on emission in the υ = 1, J = 1 → 0 transition, and 1.72 mJy in the υ = 2, J = 1 → 0 transition, respectively, for a noise bandwidth of 250 kHz. The corresponding limits for a 31.25 kHz bandwidth are 4.69 and 4.86 mJy, respectively. These upper limits improve on previous upper limits for this system by more than two orders of magnitude.